2006
DOI: 10.1002/nbm.1093
|View full text |Cite
|
Sign up to set email alerts
|

MR in oncology drug development

Abstract: This article reviews the use of MR in preclinical and clinical experiments to aid drug development. In particular it concentrates on the use of MR to study tumor microvasculature following treatment with anti-vascular agents and the use of MRS to study tumor metabolism following treatment with a variety of anti-cancer agents. The advantages and disadvantages of a variety of techniques including contrast-and noncontrast-enhanced methods are discussed and the data from clinical trials using these techniques are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…This far outweighs the tiny incidence [0.00045% of the Ͼ30 million patients who have received a particular, suspect CR (34)] of serious reaction to CR administration, and which correlates with preexisting kidney compromise. We expect the SSM to also significantly quantify the proven DCE-MRI ability to detect very early responses to anticancer therapeutic interventions with approved drugs (16) and in drug discovery (35,36). And the SSM has much more to teach us.…”
Section: Discussionmentioning
confidence: 99%
“…This far outweighs the tiny incidence [0.00045% of the Ͼ30 million patients who have received a particular, suspect CR (34)] of serious reaction to CR administration, and which correlates with preexisting kidney compromise. We expect the SSM to also significantly quantify the proven DCE-MRI ability to detect very early responses to anticancer therapeutic interventions with approved drugs (16) and in drug discovery (35,36). And the SSM has much more to teach us.…”
Section: Discussionmentioning
confidence: 99%
“…In DCE MRI, a commonly used metric that relates to the central volume principle is the initial area under curve, IAUC (17)(18)(19), which computes the area under C tiss (t) up to a stipulated time t max that encompasses a major portion of C tiss (t) (typically, t max % 60-100 sec after tracer injection). When normalized by the corresponding area under…”
Section: Convolutionmentioning
confidence: 99%
“…In DCE MRI of tumors, IAUC norm would be indicative of the combined volumes of m p and m e , and several studies have shown its usefulness as a potential biomarker in antiangiogenic drug trials (17)(18)(19). Other modifications to the IAUC metric have also been proposed, which can be sensitive to different tissue parameters (29).…”
Section: Convolutionmentioning
confidence: 99%
See 2 more Smart Citations